A consistency method of discharge detection results at solar‐blind ultraviolet based on a radiation transmission model. Issue 4 (1st March 2022) - Liu, Yunpeng; Li, Yonglin; Geng, Jianghai; Cui, Muhan; Huang, Shilong
Abstract: Solar‐blind ultraviolet (UV) discharge detection based on UV signals in the solar‐blind band from 240 to 280 nm is an effective non‐contact discharge detection method for electrical equipment, but there is still a problem that the detection results of different types of UV imagers are not comparable. To this end, by using standard light source and MODTRAN model, the relationship between the facular area and the radiant flux received by UV imagers was investigated by establishing a radiation transmission model for UV detection under different environmental conditions. Through analysis, it was found that the influence of humidity on the transmittance of the solar‐blind band in atmosphere can be neglected, and the transmittance is slightly affected by atmospheric pressure, temperature, and detection distance under conditions suitable for UV detection. Moreover, a consistency formula for UV detection results was proposed, thus forming a consistency method for detection results suitable for various types of UV imager. Finally, the feasibility of the consistency method was verified by UV discharge detection tests with a rod‐plate model and the absolute irradiance at discharge points of the rod‐plate model measured by a grating spectrometer. The consistency method is conducive to the promotion of UV discharge detection technology.